Expression of genes associated with thermal stress in goats during different seasons - MAURYA, DIVAKAR; GUPTA, MAHESH; DANGI, S S; YADAV, V P; MAHAPATRA, R K; SARKAR, M (The Indian Journal of Animal Sciences, 2013)
Leptin, interleukin-2 (IL-2) and interleukin-6 (IL-6) have role in thermoregulation in animals. Therefore, the present study was undertaken to investigate the changes in expression profile of mRNA of leptin, interleukin-2 (IL-2) and interleukin-6 (IL-6) during peak winter, moderate cold and peak summer in PBMCs of goats (Capra hircus). Blood samples were taken from the goats of 2 different regions; tropical and temperate, each having 3 age groups (n=6 in each), during all 3 seasons. PBMCs were separated from blood samples and total RNA was isolated from which cDNA was synthesized using same amount of total RNA for each sample. Real time qPCR was applied to investigate mRNA expression of examined factors. Specificity of the desired products was documented using analysis of the melting temperature and high resolution gel electrophoresis to verify that the transcripts are of the exact molecular size and further confirmed by sequence analysis. Relative expression of each factor was calculated using respective efficiency by using Pfaffl equation. Our results indicated that during winter mRNA expressions of leptin, IL-2 and IL-6 were significantly higher than summer in all 3 age groups of both tropical and temperate goats. From the results, it is concluded that significant higher mRNA expressions of all these genes during cold stress suggest possible involvement of these genes in modulating cold stress by maintaining cellular homeostasis in goats.